2018
DOI: 10.1016/j.sjbs.2017.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan treatment for skin ulcers associated with diabetes

Abstract: Infections, ulcerations, gangrene and, in severe cases, extremity amputation, are common complications among diabetic subjects. Various biomaterials have been utilized for the treatment of these lesions. Chitosan is an amino sugar with a low risk of toxicity and immune response. In this study, we evaluated chitosan topical gel and film treatments for subjects with diabetic ulcerations and wounds associated with diabetes mellitus. In a pre-experimental design, we described the result of chitosan gel and film tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Patients with a variety of ulcers were studied from November 2014 to March 2015 at the Sports Medicine Clinic of the Sonora Institute of Technology in Ciudad Obregón, Sonora, Northwest Mexico. All patients and staff involved with the study confirmed their participation through informed consent [25].…”
Section: Medical Application Of the Chitosan Membranesmentioning
confidence: 99%
“…Patients with a variety of ulcers were studied from November 2014 to March 2015 at the Sports Medicine Clinic of the Sonora Institute of Technology in Ciudad Obregón, Sonora, Northwest Mexico. All patients and staff involved with the study confirmed their participation through informed consent [25].…”
Section: Medical Application Of the Chitosan Membranesmentioning
confidence: 99%
“…Chitosan is a biopolymer that helps the healing process ( Escárcega-Galaz et al., 2018 ). Structurally, it is a linear, two-monomer polysaccharide, (1-4)-2-amino-2-deoxy-β-D-glucan (D-glucosamine) and (1-4)-2-acetamide-2-deoxy-β-D-glucan (N-acetyl-D-glucosamine).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the problems described, there is a need for research on new materials that can help the wound healing process for diabetic patients. Escárcega-Galaz et al 3 proposed a chitosan hydrogel for skin ulcers on diabetic feet (skin ulcer in the foot), and applied the treatment once every two days for three months. At the end of the study, the patients showed considerable healing of the wounds.…”
Section: Introductionmentioning
confidence: 99%